HEMATOLOGICAL PARAMETERS OF ALLOXAN-INDUCED DIABETIC RATS TREATED WITH ETHANOL EXTRACTS AND FRACTIONS OF NAUCLEA LAFILOIA LEAF - Edet, Asanga E.; Patrick, Ebong E.; Olorunfemi, Eseyin, A. (European Scientific Journal, ESJ, 2013)
Hematological parameters which have been implicated in diabetes mellitus were investigated in this study. N-hexane, ethyl acetate, butanol and methanol fractions of the ethanolic leaf extract of Nauclea latifolia were orally administered once daily for 2 weeks to diabetic rats. The levels of RBC, Hb, HCT, MCV, MCH, MCHC, PLT, PCT, MPV, PDW, WBC, lymphocyte and granulocyte were evaluated in blood. There was significant reduction (P < 0.05) in RBC and HCT levels in the treatment groups of ethyl acetate fraction (250 mg/kg) and ethanol extract (250 mg/kg) with significant increases (P < 0.05) in their MCV and MCH levels when compared with the diabetic control group. Significant increases (P < 0.05) in PLT levels of the treatment groups of ethanol extracts, n-hexane fractions and ethyl acetate fraction (100 mg/kg); PCT levels of ethanol extracts group and MPV levels of ethyl acetate fractions treatment groups was high. The treatment groups of glibenclamide, butanol, methanol, n-hexane, ethyl acetate fractions and ethanol extract (250 mg/kg) showed significant reduction (P < 0.05) in their WBC and lymphocyte levels while significant increase (P < 0.05) in granulocyte levels was noted in the treatment group of ethanol extract (100 mg/kg) when compared with diabetic control group. In conclusion, the ethanol extract proved to have anti-infective property. Some fractions, showed capabilities to boost the immune system.